CHARACTERIZATION OF PARTICULATE MATTER WITH SPECIAL REFERENCE TO PM10 And PM2.5 IN SINGRAULI COAL-FIELD - Yadav, Akhilesh Kumar (Indian Institute of Technology (Banaras Hindu University), Varanasi, 2019)
Air pollution is a matter of great concern globally due to its adverse effects on health, environment, and climate. Urbanization, industrialization, mining, vehicular emission, biomass burning, and population growth are the main contributors to air pollution. Among them, the pollution caused by coal mining in India is a concern. The existing standard for air quality emphasizes the concentration of particulate matter with specific reference to PM₁₀ and PM₂․₅. The composition of particulate matter is important, and there is a need for a thorough investigation of particulate matter in terms of concentration and composition along with size characterization. The concentration, composition, and size play an important role in adversely affecting the environment and control measures of air pollution in coal mines. Composition of particulate matter along with concentration and size now portly considered. Only, Ni, As, and Pb elements are included in the recent notification of the national ambient air quality standard of India. In opencast coal mines, airborne particulate matter, gaseous pollutants, and an air– suspended mixture of both solid and liquid particles in the atmosphere due to its adverse effects on human health, machinery and the environment are a major concern. Particularly, PM₂․₅ and PM₁₀ mass & NO₂ and SO₂ concentrations have been given special attention due to their impact on air quality and human health. The highly mechanized large mega– projects like Singrauli coalfield is facing environmental problems due to the presence of high concentrations of particulate matter in the atmosphere. Hence, a details investigation has been carried in the Singrauli coalfield of India. The objectives of this work are as follow: 1) to assess air quality status in and around coal mining complex and thermal power plants, 2) to assess the variation in concentration of particulate matter of various sizes along with nitrogen dioxide and sulphur dioxide, 3) chemical characterization of particulate matter of various sizes in terms of major, trace, and radioactive elements, 4) determination of health risk assessment in and around the mining complex, 5) to quantify the contribution of various sources of particulate matter for air quality deterioration, and 6) mitigation of particulate matter.
PhD theses submitted by the research scholar, Akhilesh Kumar Yadav (13151501), Department of Mining Engineering, IIT (BHU), Varanasi. Supervised by Professor Aarif Jamal Department of Mining Engineering Indian Institute of Technology (Banaras Hindu University) Varanasi – 221 005
Keywords: CHARACTERIZATION; PARTICULATE MATTER; PM10 And PM2.5; SINGRAULI COAL-FIELD; SINGRAULI; COAL FIELD